The Characteristics of Fairtrade Research: A Meta-Review on the Designs of Studies that examine Fairtrade Certification Effects on hired Farm Workers - Triebel, Johanna Veslemøy; Justus Liebig University Giessen (My University, 2024)
The Fairtrade International institution aims to support farmers and workers in developing countries, with a hope of ensuring equitable product prices for farmers and decent working conditions. The impacts of the fairtrade system have been examined in many studies. However, a quick review of the literature indicates that the insights of those studies are often contradictory. Since fairtrade is a huge field of research, this thesis will focus only on fairtrade’s impact on hired farm workers. It aims to explain and compare how the existing studies were carried out. By analysing the various characteristics of the studies, this paper will seek to demonstrate whether the results of certain studies are influenced by bias in the design. Furthermore, it is discussed how the quality of such a heterogeneous research field can be assessed, and on this basis, if it is possible to draw generalizable conclusions on the impact of fairtrade on hired farm workers. These objectives and questions are addressed with a descriptive approach. A systematic literature review is followed by a structured analysis of the characteristics of the studies. Therefore, a catalogue of criteria is established and used to categorize each study. The results are analysed using frequency distributions and contingency tables. 18 studies were analysed, with an average of 255 participants. Six of them were conducted in Africa, seven in Central and Latin America and three in Asian countries. Most of the studies did reveal small impacts of fairtrade, either negative or positive. To emphasize the contrast between the study characteristics, the category result tendency was introduced. This category demonstrates whether results are rather positive or rather negative, regardless of the strength of the effect. On this basis, the following characteristics occur mainly with positive tended results: a cross-sectional design (rather than longitudinal design), a sample size =< 100 (rather than a sample size > 100), a descriptive or explorative approach (rather than testing-hypotheses approach) and when not only workers but additional persons got examined (for example management staff of a company). These findings suggest that the design of the studies might have biased their results. In contrast, mixed-methods designs were revealed to be reasonably balanced in their research approaches and results, which proposes the use of mixed-methods designs for further research. Furthermore, it was revealed that most of the studies examine workers on plantations, only a few studies focussed on workers on small-farms. Moreover, on those small-farms the impacts of fairtrade were rather negative, whereas, on plantations, the impacts were often rather positive. These findings point to two important questions: why is the research on small farms that scarce? And why are the impacts of fairtrade on small-farms rather negative? It seems that fairtrade does not make a decisive impact in contributing to fairer trading conditions worldwide. This study concludes that further research is necessary, especially in the context of fairtrade on small farms. This is in order to attempt to understand the cause of the discrepancy and, the barriers and facilitators that make fairtrade work, or prevent it from working.
Keywords: Fairtrade; farm worker; rural development; global food chain; ddc:330; ddc:320; ddc:333.7